Towards Sustainable Development: Measuring Environmental Total Factor Productivity in Egypt - Al-Ayouty, Iman; Hassaballa, Hoda (European Journal of Sustainable Development, 2020)
Egypt’s heavy reliance on energy- and capital-intensive industries currently hinders its drive towards achieving sustainable development goals. This paper studies environmental total factor productivity (ETFP) for ten energy-intensive industries using the Malmquist index and data envelopment analysis (DEA) for the period 2002-2014. Through incorporating CO2 emissions by energy intensive industries, DEA helps identify both environmentally-efficient and inefficient industries. Findings indicate that: i) ETFP has remained almost unchanged for the 10 industries, with ‘technical progress’ improvement almost fully outweighed by an efficiency deterioration, ii) excluding the environmental component indeed yields overestimated total factor productivity (TFP). In its estimation of ETFP, the paper adds to exiting empirical literature since no similar estimation has been done for Egypt. Results may be relevant to other countries with similar industrial structures. Policy implications include the reliance on renewable sources of energy, bearing directly on the achievement of the seventh, ninth and twelfth SDG goals. Keywords: environmental total factor productivity; energy intensive industries; data envelopment analysis; Egypt